Brain structure and intragenic DNA methylation are correlated, and predict executive dysfunction in fragile X premutation females - Shelton, A L (Transl Psychiatry, 2016)
DNA methylation of the Fragile X mental retardation 1 (FMR1) exon 1/intron 1 boundary has been associated with executive dysfunction in female carriers of a FMR1 premutation (PM: 55–199 CGG repeats), whereas neuroanatomical changes have been associated with executive dysfunction in PM males. To our knowledge, this study for the first time examined the inter-relationships between executive function, neuroanatomical structure and molecular measures (DNA methylation and FMR1 mRNA levels in blood) in PM and control (<44 CGG repeats) females. In the PM group, FMR1 intron 1 methylation was positively associated with executive function and cortical thickness in middle and superior frontal gyri, and left inferior parietal gyrus. By contrast, in the control group, FMR1 intron 1 methylation was negatively associated with cortical thickness of the left middle frontal gyrus and superior frontal gyri. No significant associations were revealed for either group between FMR1 mRNA and neuroanatomical structure or executive function. In the PM group, the lack of any significant association between FMR1 mRNA levels and phenotypic measures found in this study suggests that either FMR1 expression is not well conserved between tissues, or that FMR1 intron 1 methylation is linked to neuroanatomical and cognitive phenotype in PM females via a different mechanism.